2018
DOI: 10.1016/j.sapharm.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to enhance effective communication during over-the-counter consultations in the community pharmacy setting: A systematic review

Abstract: Empirical evaluation of interventions using active learning techniques such as face-to-face training with role-play can improve some communication skills. However interventions that are not fully described limit the ability for replication and/or generalisability. This review identified interventions targeting pharmacy personnel. Future interventions to improve communication should consider the consumer's role in OTC consultations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Mapping the TDF to COM-B can assist researchers to identify the target for interventions that aim to change behaviour. While it is recognised that the use of behavioural theory may assist to understand behaviours, few community pharmacy-specific interventions utilise behavioural theory to develop or report interventions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mapping the TDF to COM-B can assist researchers to identify the target for interventions that aim to change behaviour. While it is recognised that the use of behavioural theory may assist to understand behaviours, few community pharmacy-specific interventions utilise behavioural theory to develop or report interventions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the first phase, a systematic literature review identified interventions targeted towards improving communication between consumers and pharmacy personnel during OTC consultations in the community pharmacy setting [47]. Focus group discussions were then conducted to determine pharmacist, non-pharmacist pharmacy personnel and consumer perspectives regarding barriers and facilitators for information exchange during OTC consultations in community pharmacies [39].…”
Section: Methodsmentioning
confidence: 99%
“…There is substantial evidence, however, that the management of the diverse range of OTC enquiries encountered in community pharmacies is sub-optimal, and that this is mainly due to inadequate information gathering and/or advice or information provision by pharmacy personnel [1,26,27,28,29,31,32,41,42,43,44,45,46]. While there has been a number of interventions to improve the exchange of information between pharmacy personnel and consumers, with varying levels of success [47], there are also studies which show that pharmacy personnel are not complying with appropriate standards [26,29,41,42,43,45].…”
Section: Introductionmentioning
confidence: 99%
“…between patients and pharmaceutical staff is associated with positive outcomes of a self-medication consultation, such as a recommendation of appropriate medicine [13,27,29,30]. However, recent evidence suggests that worldwide information exchange during self-medication consultations in the routine care shows areas needing improvement [27,28,[31][32][33][34][35].…”
Section: Competing Interestsmentioning
confidence: 99%
“…Gathering information related to the patient’s enquiry is crucial for the pharmaceutical staff to recommend an appropriate therapy and to provide appropriate advice to patients [ 27 , 28 ]. An increased amount of information exchanged between patients and pharmaceutical staff is associated with positive outcomes of a self-medication consultation, such as a recommendation of appropriate medicine [ 13 , 27 , 29 , 30 ]. However, recent evidence suggests that worldwide information exchange during self-medication consultations in the routine care shows areas needing improvement [ 27 , 28 , 31 35 ].…”
Section: Introductionmentioning
confidence: 99%